Predictors of quality of life in 102 patients with treated Cushing's disease. (2nd July 2014) - Carluccio, Alessia; Sundaram, Nina K.; Chablani, Sumedha; Amrock, Levana G.; Lambert, Jessica K.; Post, Kalmon D.; Geer, Eliza B.
Summary Objective To identify predictors for quality of life (QoL) in treated Cushing's disease (CD) and quantify patients' assessment of their disease status. Context Significant reductions in QoL exist in CD patients despite treatment. Identifying predictors of QoL is paramount to the long‐term management of these patents. Design A cross‐sectional study was conducted of patients with treated CD. Patients completed a medical history questionnaire and three validated quality of life assessments: Cushing's QoL Questionnaire (CushingQoL), Hospital Anxiety and Depression Scale (HADS) and Nottingham Health Profile (NHP). Patients 102 patients (75·7% female, mean time since surgery 7·4 years) with treated CD were included. Measurements Patients were categorized by biochemical and self‐identified disease status. Mean CushingQoL, anxiety and depression scores were compared by unpaired t‐tests. Multiple linear regressions were performed on the whole cohort to assess for predictors of impaired QoL. Results Ninety‐two per cent of the cohort met criteria for biochemical remission, but only 80·4% felt they had achieved remission. Among those with biochemical remission, those who also self‐identified as being in remission had higher CushingQoL scores than those who self‐identified as having persistent disease (P = 0·042). Anxiety (P = 0·032) and depression (P = 0·018) scores were lower, and CushingQoL scores were higher (P = 0·05) in patients who self‐identified as being in remission compared to persistence. Recovery time, BMI, gender and age were also predictors for QoL. Conclusion Our study identifies the discordance that can exist between biochemical and self‐assessed disease status and demonstrates its impact on QoL in patients with CD. These findings highlight the importance of incorporating patients' disease perceptions in their management.